Theoretical Study on Spectrum and Luminescence Mechanism of Indocyanine Green Dye Based on Density Functional Theory (DFT) - Zhao Liu; Shu-Tao Wang; Yan-Song Hu; Jia-Rong You; Yong-Sheng Xv; Jun-Qiang Lei (Journal of Chemistry)
Indocyanine green is a great near-infrared fluorescence with good luminescent properties and important medical applications. In this paper, the theoretical spectrum and orbital model of its molecular level are established. The two most probable conformations were studied, and their energies, vibrational spectra, UV-Vis absorption spectra, frontier molecular orbitals (HOMO and LUMO), and energy gaps were obtained by density functional theory (DFT) calculations, respectively. This provides a theoretical and design basis for the development of novel dyes similar to indocyanine green dyes and a reference case for improved application methods and synthetic predesign of novel fluorescent dyes.